Conservation incentives for private commercial farmers in the thicket biome, Eastern Cape, South Africa - Cumming, Tracey Lyn (Rhodes University, Faculty of Science, Department of Environmental Science, 2007)
This study sought opportunities to mitigate the pressures of land transformation and alien invader plants on commercial farm land in the thicket biome in the lower reaches of the Fish Kowie Corridor. It had two aims. Firstly, to determine the role incentives could play in mitigating these pressures. Secondly, to determine the characteristics of an incentive programme that would most effectively achieve this. In order to do this, an understanding of landowner activities, needs, opinions and barriers to behaviour; the nature of the pressures on thicket and the nature of the required behaviour to reduce these pressures; and current and past institutional arrangements needed to be achieved. This was done predominantly through a current literature review and personal interviews with landowners and key informants. These findings were used to make recommendations for an effective incentive programme. Landowners showed a preference towards tangible incentives, in particular management assistance, financial compensation and law enforcement. They indicated an aversion to an incentive programme implemented by a government agency, particularly district and provincial government. Rather, landowners showed a propensity towards a nongovernment organisation (NGO) or a farmers group implementing an incentive programme. It was recommended that the two major pressures, namely land transformation and alien invader plants, required different interventions by different agencies in order to be mitigated. The pressure of land transformation required a stewardship model response, with the primary drive being a non-contractual environmental extension service to landowners. The extension service should focus on promoting pro-conservation practises, raising awareness and disseminating information. It should also build a relationship of trust between landowners and the implementing agency. The pressure of alien invader plants would be most effectively addressed through the Working for Water programme. Tangible incentives must be provided to the landowner to induce the costly exercise of alien invader plant control. In particular, the high cost of labour must be addressed. The regulatory incentive of applying laws requiring landowners to control alien invader plants on their land should also be enforced.
Keywords: Landowners -- South Africa -- Eastern Cape; Invasive plants -- South Africa -- Eastern Cape; Plant conservation -- South Africa -- Eastern Cape; Conservation of natural resources -- South Africa -- Eastern Cape